Cys18-Cys137 Disulfide Bond in Mouse Angiotensinogen Does Not Affect AngII-Dependent Functions In Vivo. Issue 4 (April 2015) - Wu, Congqing; Xu, Yinchuan; Lu, Hong; Howatt, Deborah A.; Balakrishnan, Anju; Moorleghen, Jessica J.; Vander Kooi, Craig W.; Cassis, Lisa A.; Wang, Jian-an; Daugherty, Alan
<x xml:space="preserve">Abstract</x> Renin cleavage of angiotensinogen (AGT) releases angiotensin I (AngI) in the initial step of producing all angiotensin peptides. It has been suggested recently that redox regulation of a disulfide bond in AGT involving Cys18-Cys137 may be important to its renin cleavage efficiency in vivo. The purpose of this study was to test this prediction in a mouse model by comparing AngII production and AngII-dependent functions in mice expressing wild-type AGT versus a mutated form of AGT lacking the disulfide bond. Wild-type (hepAGT+/+) and hepatocyte-specific AGT-deficient (hepAGT−/−) littermates were developed in an low-density lipoprotein receptor −/− background. hepAGT+/+ mice were injected intraperitoneally with adeno-associated viral (AAV) vector containing a null insert. hepAGT−/− mice were injected with AAV containing a null insert, wild-type AGT or Cys18Ser and Cys137Ser mutated AGT. Two weeks after AAV injection, mice were fed a Western diet for 12 weeks. Administration of AAV containing either form of AGT led to similar plasma AGT concentrations in hepAGT−/− mice. High plasma renin concentrations in hepAGT−/− mice were suppressed equally by both forms of AGT, which were accompanied by comparable increases of plasma AngII concentrations similar to hepAGT+/+ mice. AAV-driven expression of both forms of AGT led to equivalent increases of systolic blood pressure and augmentation of atherosclerotic lesion size in hepAGT−/− mice. These measurements were comparable to systolic blood pressure and atherosclerotic lesions in hepAGT+/+ mice. These data indicate that the Cys18-Cys137 disulfide bond in AGT is dispensable for AngII production and AngII-dependent functions in mice.